2015
DOI: 10.15406/mojap.2015.01.00018
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofacial Assessment of Indian Americans and Its Significance – An Anthropometric Study

Abstract: Background: For the perception of facial attractiveness, the orbital region in the face acts as a key determinant factor. The Orbitofacial measurements vary with sex and race. Orbital region in the face is one of the most important regions in plastic, reconstructive and ophthalmic surgery and anthropometric evaluation. There are no reports available on the Orbitofacial anthropometry in Indian American population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(34 reference statements)
2
7
0
Order By: Relevance
“…In the literature, a good many studies have been examined the en-en 1,2,4–6,8–24,26,28–37,39–48,50–52,54,56 and ex-en 1,2,6,8–11,16,18,19,21,23,26,29–33,37,41–50,54,56 . While, in most of these studies, average values of the en-en were reported as having a range of 30 to 35 mm and ex-en were reported as having a range of 28 to 35 mm similar to this study, it is observed that there are higher en-en values especially the studies on Chinese, 14–18 Asians, 11 Korean American, 29 and Nigerian 36 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the literature, a good many studies have been examined the en-en 1,2,4–6,8–24,26,28–37,39–48,50–52,54,56 and ex-en 1,2,6,8–11,16,18,19,21,23,26,29–33,37,41–50,54,56 . While, in most of these studies, average values of the en-en were reported as having a range of 30 to 35 mm and ex-en were reported as having a range of 28 to 35 mm similar to this study, it is observed that there are higher en-en values especially the studies on Chinese, 14–18 Asians, 11 Korean American, 29 and Nigerian 36 .…”
Section: Discussionsupporting
confidence: 66%
“…Various studies have been conducted in the literature for different populations, race and ethnic groups such as, African-American 8–10 , Asian , 11 Caucasian , 4,12,13 Chinese , 14–19 Ibibio people , 20 Indian , 21 Indian American , 22,23 Itsekiri people , 24 Japanese , 25 Korean , 26–28 Korean American , 29 Latvian , 30 Malays , 31 Malaysian Indian , 32 Mexican , 25 Northern Sudanese , 33 North American Caucasian , 34,35 Nigeria , 36 Persian/Iranian , 37–39 Saudi Arabian , 40,41 Sudanese , 42 South Indian , 43 Thai , 19 Turkish , 1,2,5–7,44–50 Urhobo , 24 and Vietnamese 19 . These studies and their results are summarized in Supplementary Digital Content, Table 4, http://links.lww.com/SCS/C63.…”
Section: Discussionmentioning
confidence: 99%
“…A third reading was taken in case, if the initial two measurements showed a large discrepancy, and finally the two closer readings out of the three were used ( Fig. 3 ) [ 14 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study performed by Sadacharan [ 13 ] with 100 Indian American female face dealt with facial proportions. Sadacharan [ 14 15 ] performed an anthropometric studies of horizontal thirds of the face and proportions of lowerface height and orbitofacial assessment in Indian Americans. However, there are no reports available on the facial proportions in Indian American men.…”
Section: Introductionmentioning
confidence: 99%
“…Normal values of canthal distance helps and serves as a guide to diagnose the pathologies and for early surgical intervention. Knowledge of subtle morphological changes in Dysmorphic syndromes which were diagnosed based on molecular and cytogenetic techniques will help in directing towards the useful diagnostic test [6] .…”
Section: Introductionmentioning
confidence: 99%